Moringa oleifera Leaf Powder Dietary Inclusion Differentially Modulates the Antioxidant, Inflammatory, and Histopathological Responses of Normal and Aeromonas hydrophila-Infected Mono-Sex Nile Tilapia (Oreochromis niloticus) - Seham El-Kassas; Nesreen Aljahdali; Safaa E. Abdo; Fatima S. Alaryani; Eman M. Moustafa; Radi Mohamed; Wesam Abosheashaa; Esraa Abdulraouf; Mohamed Atef Helal; Manal E. Shafi; Mohamed T. El-Saadony; Karima El-Naggar; et al. (Frontiers in Veterinary Science, 2022)
This study aimed to detect the impact of Moringa oleifera leaf powder dietary inclusion on the antioxidant and innate immune responses of mono-sex Nile tilapia fingerlings. A total of 180 fingerlings were allocated in a random method into three groups with triplicate each. One group (1st group) received the control diet (basal diet (BD) free of moringa) and the other groups (2nd and 3rd) fed BD containing M. oleifera leaf powder at 5 and 10% of the diet, respectively. After 6 weeks of feeding, fish were randomly redistributed into four replicates and rested for 24 h. Then, each fish in the first two replicates was injected with 0.2 mL of PBS, while the others were injected with 0.2 mL of A. hydrophila suspension (1.8 × 106 CFU/mL). Healthy fish fed on M. oleifera leaf powder showed enhanced immune response manifested by significant increases in phagocytic and lysozyme activities with a marked H/L ratio (P < 0.05). In addition, significant alterations of the lymphocytic and heterophilic population in circulation with increasing infiltration in tissue such as the spleen were noticed. Also, M. oleifera significantly upregulated the antioxidants, CAT and GPx, proinflammatory cytokines, IL1-β, IL-8, and IFN-γ relative mRNA levels. On the other hand, following A. hydrophila challenging conditions, M. oleifera caused downregulations of IL1-β, IL-8, and IFN-γ transcription levels, and also lowered the CAT and GPx mRNA levels. In addition, a marked reduction of leukocytic infiltration plus a significant improvement of the degenerative changes in intestinal architecture has occurred. So, M. oleifera leaf powder can be included in the fish diet to enhance immune response under normal health conditions and lower the infection-associated inflammatory response.